Meningkatkan Keputusan Pembelian Make Up Brand Lokal Wardah Melalui Celebrity Endorser, Brand Image dan Product Quality Pada Mahasiswi S1 Universitas Sarjanawiyata Tamansiswa - Haque Rifky Anggela Putri; Muinah Fadhilah; Bernadetta Diansepti Maharani (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2021)
This study aims to determine that influence on celebrity endorser, brand image and product quality on buying decisions. The research method uses non probability sampling method. The research sample was 100 active undergraduate students at Sarjanawiyata Tamansiswa University Yogyakarta and then the data were processed using descriptive analysis, validity test, reliability test, normality test, multicollinearity test, heteroskesdacity test, and multiple linear regression. The results show that, celebrity endorser has a significance value of 0.004 and product quality has a significance value of 0.000 then celebrity endorser and product quality have effect on buying decisions. However, brand image not gives effect on buying decisions as evidenced by a significance value of 0.645. The results of the F test show simultaneously celebrity endorser, brand image, product quality that affects on buying decision a significance value of 0.000 is obtained.